About primary metaphors - Lima, Paula Lenz Costa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
One important contribution to the Contemporary Theory of Metaphor id Grady's Primary Metaphor Hypothesis (1997), which claims that the emergence and nature of conceptual metaphors are often grounded in more experiential metaphorical patterns, called primary metaphors. The new hypothesis changes considerably the ideas concerning the generation of metaphors, in comparison to the former view. In this paper we discuss some of these mains changes, namely the caracteristics of source and target domain, the fundamental construct, and the licensing of metaphorical expressions.